UPAYA PENINGKATAN HASIL BELAJAR PASSING DAN CONTROL DALAM SEPAK BOLA MENGGUNAKAN PERMAINAN KUCING - KUCINGAN - Benny Widya Priadana; Edi Setyanto; Alif Yuanita Kartini (Sekolah Tinggi Pariwisata Mataram, 2020)
In physical education learning there are several obstacles that occur in the process of passing and control learning in soccer for fifth grade students of SDN Mori 01, Trucuk District, Bojonegoro Regency 2019. One way that can be done to improve student learning outcomes is through classroom action research, making a learning model that appeals to students with the learning approach to play. The problem in this study is whether the implementation of passing and control learning using cat - and - mouse games can improve the quality and learning outcomes of fifth grade students of SDN Mori 1, Trucuk District, Bojonegoro Regency in 2019? The purpose of this study was to determine the application of passing and control learning through the cat-cat game media can improve the quality and learning outcomes for students of class V SDN Mori 01 Trucuk District, Bojonegoro Regency 2019. in physical education subjects. This research was conducted at SDN Mori 1, Trucuk District, Bojonegoro Regency. The sample in this study was class V students, amounting to 31 students. This research is a class action research consisting of two cycles where each cycle consists of 4 stages, namely planning, action, observation (observation) and reflection. Data collection techniques in this study are: observation methods, documentation methods, and test methods. The results showed that the application of play methods could improve the results of learning passing and control in fifth grade students of SDN Mori 1, Trucuk District, Bojonegoro Regency 2019. From the analysis results obtained there was an increase in student learning outcomes from the first cycle to the second cycle. The average value of passing and control learning outcomes in the first cycle (71.59), the second cycle (83.84). So that the increase in learning outcomes from the first cycle to the second cycle is (12.25). While the number of students who were declared complete in the first cycle were 11 students (35.5%) and the second cycle were 26 students (83.9%). The conclusion of this study, that passing and control learning through playing cat and mouse media for fifth grade students of SDN Mori 01, Trucuk District, Bojonegoro Regency in 2019 can improve student learning outcomes. It is recommended that every physical education teacher is always creative and innovative in making learning models, with the aim of student learning outcomes can be improved.